Estudo comparativo das técnicas de fixação óssea em fraturas de côndilo mandibular através de análise por elementos finitos - Conci, Ricardo Augusto (2014)
Mandibular condylar fractures are a theme of great importance within Oral and Maxillofacial Surgery due to their high incidence among facial fractures, and to numerous discussions regarding forms of treatment, surgical approaches, and the type of material used for fracture fixation. Treatment can be either surgical or nonsurgical, and depends upon certain situations and directions. When the choice is for surgical treatment proper fracture reduction and efficient internal fixation must be pursued to achieve good final results. Numerous plate configurations, whether or not isolated, with various shapes and sizes, are used for the surgical resolution of condylar fractures. In order to enhance the advantages and minimize the disadvantages of fixation techniques, the Neck Screw was developed, aiming at the necessary stability for proper fixation through a dynamic compression system that could increase the contact between the fractured stumps, and, at the same time, assist at the time of fracture reduction. The purpose of this study was to assess the fixation and stability of mandibular condylar fractures, and to compare three fixation techniques, in that the first configuration had a 2.0 mm plate with 4 holes, and with 6-mm-long screws, the second configuration had two plates ─ one of 1.5 mm and the other of 2mm ─-both with 4 holes, and with 6-mm-long screws, and the last had a Neck Screw. The results showed improved stability when using two plates, in regard to displacement of the fractures, deformation of the synthesis materials, and minimum and maximum tension values. The results with the Neck Screw were satisfactory, similar to those found when using a Mini-Plate, and it is thus an alternative for the reduction and fixation of condylar fractures, provided it is correctly prescribed, and follows an appropriate surgical sequence and technique